Absolute convergence of fourier series of superpositions of functions - Akishev, G.A. (Allerton Press, Inc., 2009)
In this paper we establish conditions for the absolute convergence of series of Fourier coefficients with respect to a generalized Haar system of a superposition of two functions.
Keywords: Fourier coefficients; Haar system; superposition